2021
DOI: 10.3390/antibiotics10040447
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Uropathogens Isolated from Patients Hospitalized in District Hospital in Central Poland in 2020

Abstract: The aim of this study was to determine antibiotic resistance patterns and the prevalence of uropathogenes causing urinary tract infections (UTIs) in patients hospitalized in January–June 2020 in central Poland. Antimicrobial susceptibility testing was performed using the disk-diffusion method. Escherichia coli (52.2%), Klebsiella pneumoniae (13.7%), Enterococcus faecalis (9.3%), E. faecium (6.2%), and Proteus mirabilis (4,3%) were most commonly isolated from urine samples. E. coli was significantly more freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 48 publications
6
26
1
1
Order By: Relevance
“…As expected, the most commonly identified uropathogen was E. coli, responsible for almost two-thirds of the recorded cases of UTI. This finding is in accordance with multiple recent studies [16][17][18][19], which found it to be the main etiological agent in up to 95% of the UTIs. The second most isolated bacteria were Klebsiella spp., encountered in 76 cases (21.4%), of which K. pneumoniae was by far the most common species, an aspect in accordance with the results reported by several recent studies [4,17,18,20], even though a recent study conducted in another region of Romania reported K. pneumoniae as the leading etiology in some settings [21].…”
Section: Discussionsupporting
confidence: 93%
“…As expected, the most commonly identified uropathogen was E. coli, responsible for almost two-thirds of the recorded cases of UTI. This finding is in accordance with multiple recent studies [16][17][18][19], which found it to be the main etiological agent in up to 95% of the UTIs. The second most isolated bacteria were Klebsiella spp., encountered in 76 cases (21.4%), of which K. pneumoniae was by far the most common species, an aspect in accordance with the results reported by several recent studies [4,17,18,20], even though a recent study conducted in another region of Romania reported K. pneumoniae as the leading etiology in some settings [21].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, carbapenem antibiotics have been recognized as effective treatments for antibiotic-resistant UTIs, and this class of antibiotics is now widely used in the treatment of complex microbial infections (25). In the current study, amikacin (11%) and imipenem (5%) showed the highest drug activity against uropathogenic isolates, which was in line with the results of other studies conducted in Iran, Pakistan, and Mexico (21,22,26).…”
Section: Discussionsupporting
confidence: 90%
“…The increased diversity of urinary pathogens in patients with advanced age was further verified by the findings of Kot et al, noting the increasing importance of Enterococcus spp. and P. mirabilis as uropathogens in Polish patients [ 7 ]. In a rare study focusing on the 10-year epidemiology of suprapubic bladder aspirates, Gajdács et al found that around half of the samples originated from patients aged ≥ 65; out of these samples, almost one-third (32.6%) were culture-positive (defined as ≥10 2 CFU/mL), with Enterococcus spp., E. coli and Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the anatomical site affected, UTIs may be classified as upper UTIs (UUTI or pyelonephritis) or lower UTIs (LUTI, which may present as (in decreasing incidence) cystitis, urethritis and prostatitis). In a clinical sense, UTIs may be further divided into uncomplicated and complicated UTIs, depending on the presence of factors facilitating bacterial colonization in the urinary tract (e.g., a structural abnormality) or decreasing therapeutic efficacy [ 6 , 7 ]. Members of the Enterobacterales order are the facultative pathogens most commonly implicated as causative agents for UTIs in the general population.…”
Section: Introductionmentioning
confidence: 99%